Hemicellulose: Structure, chemical modification, and application. (May 2023) - Rao, Jun; Lv, Ziwen; Chen, Gegu; Peng, Feng
Abstract: Lignocellulose has been extensively researched over the past decades in response to the growing global significance of renewable resources and environment-friendly materials. Hemicellulose is a large family of polysaccharides present in the primary and secondary cell walls of all land plants, fresh-water plants, and some seaweeds. It has gained significant attention in the development of hemicellulose-based functional polymeric materials owing to its distinct features such as environment-friendliness, renewability, and biodegradability. Recent studies have focused on the isolation, structural characterization, and chemical modification of hemicellulose and the preparation of hemicellulose-based materials. This review, comprehensively elaborates the preparation of hemicellulose-based functional polymeric materials via chemical modification, including the structures and properties of hemicellulose; design strategies for harnessing hemicellulose; and various forms of hemicellulose-based functional polymeric materials such as nanoparticles, films and coatings, hydrogels and aerogels, carbon quantum dots, porous carbons and catalysts. This review provides an update on hemicellulose-based functional materials, with a focus on their controlled-release, adsorption, biosensing, packaging, catalytic conversion, and electrode applications. Future perspectives on challenges and opportunities in the research field of hemicellulose are briefly highlighted. Graphical abstract: Illustration of chemical modification toward hemicellulose-derived functional polymeric materials. Image, graphical abstract